Is her silence or scream? The dilemma of abused women (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
Selected for this test, the subject of battered women was a decision supported by the need to know, understand, correct and clarify prejudices and misconceptions about what you feel, think and have abused women and at the same time, awakening sensibilities , raise awareness and invite participation preventive and corrective for ending the problem of violence against women. For study and analysis began by examining what it is specifically the abuse of women, for which it was considered vital, examine the statements of a number of experts who have defined and developed this theme from different disciplines such as forensics, psychiatry or gender studies, exposing the main approaches, names and descriptions that have been made of the phenomenon and its concrete manifestations sufferers.